Spectrum of underlying diseases in syncope and treatment of neurally-mediated syncope in children and adolescents over the past 30 years: A single center study - Cui, Yaxi; Liao, Ying; Zhang, Qingyou; Yan, Hui; Liu, Ping; Wang, Yuli; Sun, Yan; Xu, Wenrui; Liu, Xueqin; Du, Junbao; Jin, Hongfang (Frontiers in Cardiovascular Medicine, 2022)
Background Syncope is the primary cause of transient loss of consciousness, which causes severe physical and mental burdens to children and adolescents. Objective The study was designed to analyze the spectrum of underlying diseases of syncope and treatment options for neurally-mediated syncope (NMS) in Chinese children and adolescents. Methods Medical records including history, physical examination, blood biochemistry, standing test, head-up tilt (HUTT), sitting-up test, electroencephalogram (EEG), electrocardiogram (ECG), and echocardiography were retrospectively studied in children and adolescents admitted to the National Pediatric Syncope Center, Department of Pediatrics, Peking University First Hospital between 1992 and 2021. All the data were collected from the Beijing Kaihua Medical Management System (Kaihua, Beijing, China). Children who met the syncope diagnostic criteria were enrolled in the study. The spectrum of the underlying diseases of syncope in children and adolescents and the treatment options of NMS were analyzed. Results A total of 1,947 children and adolescents with syncope were admitted, including 869 males (44.63%) and 1,078 females (55.37%) aged 1–18 years, with an average age of 11.1 ± 3.1 years. The number of children and adolescents with syncope displayed a gradually increasing trend between 1992 and 2021 except after 2020. NMS proportion increased, and the proportion of unexplained syncope decreased (χ2 = 128.839, P < 0.01). The treatment options of NMS mainly included autonomic nervous function exercise (549, 34.46%), oral rehydration salt (ORS; 445, 27.94%), metoprolol (219, 13.75%), midodrine (120, 7.53%), ORS plus metoprolol (139, 8.73%), ORS plus midodrine (120, 7.53%), and pacemakers (1, 0.06%). Patients with vasovagal syncope (VVS) coexisting with postural orthostatic tachycardia syndrome (POTS) were more likely to take pharmacological treatments than those with VVS or POTS only (χ2 = 41.696, P < 0.01). Conclusion The number of children with syncope displayed an increasing trend before 2020, and the proportion of unexplained syncope decreased. Autonomic nervous function exercise was the most common treatment for children and adolescents with NMS. Children with VVS coexisting with POTS were more likely to receive pharmacological treatments than those with either.